Laparotomy for organ evisceration from abdominal stab wounds: A South African experience. Issue 1 (January 2019) - Kong, Victor Y.; Weale, Ross; Blodgett, Joanna M.; Buitendag, Johan; Bruce, John L.; Laing, Grant L.; Clarke, Damian L.
Abstract: Introduction: Organ evisceration following abdominal stab wound (SW) is currently considered as an absolute indication for mandatory laparotomy due to the high incidence of associated intra-abdominal injuries, but literature describing the spectrum of organ injury encountered is limited. Materials and methods: We reviewed our experience of 301 consecutive patients who were subjected to mandatory laparotomy over an eight-year period at a major trauma centre in South Africa. Results: Of the 301 patients with organ evisceration, 92% were male (mean age: 28 years). Ninety per cent (270/301) of the laparotomies were positive (85% (229/270) therapeutic, 15% (41/270) non-therapeutic). The frequencies of eviscerated organs were small bowel (70%), large bowel (26%), and stomach 3%. Three (1%) patients had combined evisceration of more than one of the above organs. The most commonly injured organs were small bowel and large bowel. The mean length of hospital stay was nine days. Seven patients required intensive care admission. The morbidity rate was 21% and mortality was 2%. Conclusions: The spectrum of injury associated with abdominal SW with organ evisceration is similar to smaller published series. Multiple organ injuries are common. The most commonly eviscerated organs were small bowel, large bowel and stomach, while the most commonly injured organs were small bowel and large bowel.